نموذج شبكة عصبية صنعيَّة للتنبؤ بالتبخر الشهري في منطقة حماه - عباس ماريا (Latakia University Journal -Engineering Sciences Series, 2018)
التبخر هو أحد العناصر الأساسية للدورة الهيدرولوجية وضروري للعديد من الدراسات مثل الموازنة المائية, تصميم أنظمة الري وإدارة الموارد المائية, ويتطلب تقديره معرفة العديد من العناصر المناخية. على الرغم من أن هناك صيغاً تجريبيَّةً متوفرةً لتقدير التبخر, ولكن أداء هذه الصيغ غير دقيق بسبب الطبيعة المعقدة لعملية التبخر. لذلك فإن هذا البحث يهدف لوضع نموذج شبكة عصبية صنعيَّة للتنبؤ بالتبخر الشهري في منطقة حماه باستخدام ثلاثة عناصر مناخية هي درجة الحرارة, الرطوبة النسبية وسرعة الرياح. من أجل ذلك فقد بُني النموذج باستخدام مكتبة nntool-box إحدى أدوات الـ MATLAB. استُخدمت الشبكة العصبية الصنعيَّة ذات التغذية الأمامية و الانتشار العكسي للخطأ بطبقة خفية واحدة لبناء النموذج. وتم تقييم شبكات مختلفة بعدد مختلف من العصبونات وبتغيير دوال التفعيل المستخدمة في كل طبقة. واستُخدم جذر متوسط مربع الخطأ (RMSE) لتقييم دقة النموذج المُقترح. وقد بينت الدراسة أن الشبكة العصبية الصنعيَّة ذات الهيكلية (3-14-1) هي الأفضل للتنبؤ بالتبخر في منطقة حماه حيث كانت قيمة RMSE تساوي (21.5mm/month) وقيمة <!–?mso-application progid="Word.Document"?–> 12R2"> مساوية (0.97). توصي الدراسة باستخدام أنواع أخرى من الشبكات العصبية لتقدير التبخر. The evaporation is one of the basic components of the hydrologic cycle and it is essential for studies such as water balance, irrigation system design and water resource management, and it requires knowledge of many climatic variables. Although, there are many empirical formulas available for evaporation estimate, but their performances are not all satisfactory due to the complicated nature of the evaporation process. Accordingly, this paper is an attempt to assess the potential and usefulness of ANN based modeling for evaporation prediction from HAMA by using temperature, relative humidity and wind velocity. The mathematical model was built by the (nntool-box), which is one of the MATLAB tools. The feed forward back propagation network with one hidden layer has been utilised to construct the model. Different networks with different number of neurons were evaluated. Root Mean Squared Error (RMSE) was employed to evaluate the accuracy of the proposed model. The study shows that ANN (3-14-1) was the best model with RMSE (21.5mm/month) and <!–?mso-application progid="Word.Document"?–> 12R2"> (0.97). This study suggests using other types of neural networks for estimation of evaporation